Otimização do tratamento de efluente de matadouro e frigorífico de suínos pela eletrofloculação e combinação eletrofloculaçào/coagulação orgânica - Orssatto, Fábio (2017)
This trial aimed at evaluating the electrofloculation performance and its combination with organic coagulation to treat effluents from a swine slaughterhouse and packing plant. This thesis was written and composed of three papers. The first one reports on the removal of COD, turbidity, color, TKN and total phosphorus in the studied effluent according to the electroflocculation technique. It also optimized variables such as potential differential (pd) and hydraulic retention time (HRT) in a batch reactor of electroflocculation using aluminum electrodes. The second paper aimed at evaluating the removal of COD, turbidity, color and TKN from the effluent by electrochemical technique and optimized variables as electric current and HRT in a continuous flow reactor of electroflocculation using aluminum electrodes. The third paper aimed at evaluating the removal of COD, turbidity, color and TKN in the effluent using the combination of electroflocculation / organic coagulation technique. It also optimized variables such as electric current, HRT and tannin-based coagulant concentration in a batch reactor. The effluent used in this study comes from a swine slaughterhouse in the western region of Paraná. For the first paper, the main results were: maximal removal of 99.28% for turbidity, 98.93% for color, 81.01% for COD, 67.15% for TKN and 99% for total phosphorus. According to the statistical analysis, it was possible to obtain mathematical models as well as removal of analyzed parameters, but phosphorus. When the desirability function was calculated, the best optimized treatment conditions were at 30 minutes for HRT and 20 volts for pd, corresponding to 0.86 A of electric current and a 17.2 mA cm-2 current density. The analysis of residual aluminum in the effluent treated in the essays recorded a high concentration, which varied from 15.254 to 54.291 mg L-1. For each cubic meter (m3) of effluent treated by electroflocculation, 10.75 kWh of electric energy and 0.18036 kg of aluminum were used, with a cost of R$ 7.90 m-3. While for the second paper, the main results were: 74.47% of maximum efficiency for turbidity, 91.76% for color and 61.07% for COD. But the system was not efficient for TKN removal, since the maximum removal percentage was 20%. Based on the statistical analysis, it was possible to obtain mathematical models to remove the analyzed parameters. And, when desirability function was calculated, the best optimized treatment conditions were at 18 minutes for HRT, 1.5 A for electric current and a current density of 16.67 mA cm-2. The residual aluminum analysis recorded a concentration range from 1.21 to 4.61 mg L-1. At each cubic meter (m3) of treated effluent, 5.17 kWh of electrical energy and 0.0938 kg of aluminum were used, with a cost of R$ 3.84 m-3. Finally, the main results of the third paper were: the maximum efficiency of removal for turbidity was 98.37%, color was 97.82%, COD was 64.73% and TKN was 65.57 %. Based on the statistical analyses, it was possible to obtain mathematical models to remove parameters of color and turbidity. And when desirability function was calculated, the best optimized treatment conditions were at 10 minutes for HRT, 0.774 mL L-1 of coagulant concentration based on tannin, 0.68 A for electric current and a 13.6 mA cm-2 current density. When analyzing the residual aluminum in the effluent treated during the studied tests, a concentration range from 0.0 to 2.11 mg L-1 was observed. For each cubic meter (m3) of effluent treated by electrocoleculation / organic coagulation combination, 2.96 kWh for electric energy and 0.0475 kg aluminum were used, resulting in R$ 3.49 m-3 cost. The electroflocculation technique and the combination of electroflocculation and organic coagulation were good alternatives to remove pollutants from the studied effluent from swine slaughterhouse and packing plant.